Can the promotion of child-focused activities influence gambling perceptions and behaviors in gambling venues? - Bestman, A.; Thomas, S.; Randle, M.; Pitt, H.; Daube, M.; Pettigrew, Simone (Springer New York LLC, 2016)
Introduction: Gambling venues in New South Wales (NSW), Australia, promote themselves as ‘family friendly’ spaces within communities that provide a range of social and leisure activities. However, the majority of gambling venue profits in Australia are attributed to one potentially harmful product, Electronic Gambling Machines (EGMs or pokies). There has been little research that explores how gambling venues promote both gambling and nongambling activities, and the role that marketing tactics may have in shaping individuals’ perceptions and behaviors whilst in the gambling environment. Methods: This research used a mixed-methods, web-based content analysis to explore the gambling and non-gambling (including family- and child-focused) activities promoted on 65 Club websites in regional NSW. Data were analyzed based on frequency counts of coded data. Results: This research found that marketing for both gambling activities and activities specifically for children and families (non-gambling activities) were heavily promoted on venue websites. A conceptual model is proposed that predicts a ‘shaping pathway’ by which gambling environments may promote gambling behaviors within the community. Conclusions: We propose that the promotion of family and child focused activities in gambling environments is a marketing strategy that may be influential on an individual’s gambling behavior, whereby the promotion of child and family activities draws consumers to the venue, however the actual long-term behavior is the use of gambling products at the venue. We hypothesize that this may be particularly harmful for children who are exposed to these gambling environments from an early age.